Triple Layer Business Model Canvas Design of Arabica Coffee Agroindustry Supply Chain in Bandung Regency - Mochamad Adieb Sultan; C. Furqon; Fanji Wijaya (Research Synergy Foundation, 2021)
The coffee industry is an industry that needs to be considered because coffee is one of the commodities that give a lot of impact to the welfare of farmers. The tendency of farmer groups in the coffee industry, they still do not understand good cropping patterns, as well as the benefits obtained by farmers if they manage cropping patterns so that the production process has an impact on improving welfare. Therefore, this study aims to develop a coffee business pattern and explore the business model built using the Business Model Canvas. Descriptive analytic methods and qualitative approaches are considered in this study. Data was collected through in-depth interviews, discussions with farmer groups, and observation. SWOT analysis was used to formulate TLBMC. The results of the study revealed that the cropping pattern and business of coffee farmer groups were in a growing position. Sustainable business development is depicted in TLBMC.